Expression of Notch signaling pathway during osteoarthritis in the temporomandibular joint. Issue 8 (August 2017) - Lan, Lingli; Jiang, Yangmei; Zhang, Weina; Li, Ting; Ying, Binbin; Zhu, Songsong
Abstract: Purpose: Our study aim was to characterize the expression of Notch molecules during temporomandibular joint osteoarthritis (TMJOA), thus exploring the mechanism and roles that Notch signaling possibly plays in the initiation and progression of TMJOA. Materials and methods: A total of 126 mice were divided randomly into experimental groups, a sham-surgery group and a normal control group. In the experimental group, total discectomy was performed in the right temporomandibular joint (TMJ) to induce TMJOA; the sham-operation group underwent the same procedure without disc removal, and the normal control group was left undisturbed. Fourteen mice in each group were sacrificed in batches respectively at 1, 2, and 4 weeks postoperatively. Histology was performed to examine TMJOA in eight condyles each group, and a modified Mankin scoring system was used for evaluation. Immunohistochemistry was carried out to characterize the expression of the Notch markers Notch1, Jagged1, Hes1, and Hes5. Real-time polymerase chain reaction (RT-PCR) was performed for further detection and analysis of Notch markers in six condyles in each group. Results: Notch1, Jagged1, and Hes5 were activated in the experimental group, with expression levels that increased dramatically over time, whereas the control group showed no fluctuation. Hes1 expression was suppressed at the beginning but was up-regulated afterward. Conclusions: Our data suggest that Notch signaling is activated in TMJOA with a much more abundant expression in osteoarthritis cartilage.